ChemInform Abstract: Structure and Optical Properties of Cubic Gallium Oxynitride Synthesized by Solvothermal Route. Issue 24 (23rd May 2013) - Oberlaender, Andreas; Kinski, Isabel; Zhu, Wenliang; Pezzotti, Giuseppe; Michaelis, Alexander
Abstract Cubic gallium oxynitride is synthesized by solvothermal processing of a gallium ethylene diamine complex and H2O (autoclave, 200 °C, 1 d).